TINJAUAN SISTEMATIS EFEKTIVITAS LAYANAN TELEFARMASI OLEH APOTEKER TERHADAP HASIL KLINIS DAN KEPUASAN PASIEN - Adji, Adji Prayitno Setiadi; Yosi, Yosi Irawati Wibowo; Rahman, Abdur (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Telepharmacy is a rapidly expanding form of remote pharmaceutical care, especially since the COVID-19 pandemic, aimed at improving access to and the quality of pharmaceutical services. Despite its widespread implementation, the effectiveness of this service remains a topic of debate. Therefore, this study aims to evaluate the types and effectiveness of telepharmacy services provided by pharmacists through a systematic review. This study employed a systematic review approach following the PRISMA 2020 guidelines. Data sources were obtained from PubMed and Oxford Journal databases using relevant keywords such as ‘effectivity,’ ‘effectiveness,’ and ‘telepharmacy.’ The process involved study identification, screening, quality assessment, and data extraction, resulting in 24 articles that met the inclusion criteria. Telepharmacy services identified across the studies were categorized into four main types: 1) remote pharmacist consultation (n=10), 2) drug information provision (n=7), 3) therapeutic drug monitoring (n=5), and 4) electronic medication dispensing (n=2). Evaluation of telepharmacy effectiveness demonstrated significant improvements in several aspects, including: 1) clinical outcomes (6 out of 9 studies; p = 0.019–0.048), 2) patient satisfaction (3 out of 4 studies; p = 0.018–0.041), 3) medication adherence (12 out of 15 studies; p = 0.002–0.040), and 4) cost efficiency (all 4 studies; p = 0.021–0.048). The findings of this systematic review indicate that telepharmacy services are generally effective in improving patient clinical outcomes, patient satisfaction with services, medication adherence, and treatment cost efficiency.